Epidemiology of Streptococcus agalactiae (Group B Streptococci) in Dublin Maternity Hospitals - Dore, Neil (Trinity College (Dublin, Ireland). Department of Microbiology, 2002)
Streptococcus agalactiae (Group B Streptococci) are Gram-positive encapsulated cocci distinguished from other streptococci by their narrower zones of P-haemolysis. Group B Streptococci (GBS) was first described as an important pathogen in the 1970's and since that time has remained the primary cause of bacterial infection in new-born babies, resulting in disease at birth and up to 3 months of age. GBS often colonises the vagina, although carriage here may be intermittent. At any one time, the vaginae of approximately a quarter of all women of childbearing age in Ireland are colonised with GBS This organism becomes particularly important in childbirth especially if there are signs of infection, GBS causes two types of infection in new-born babies depending on time of infection onset: termed early and late-onset. A number of predisposing factors, in addition to vaginal carriage during pregnancy indicate an increased risk of infant GBS sepsis and suggest prompt antimicrobial treatment. These factors include obstetric complications, low birth weight, foetal hypoxia, the presence of GBS in the maternal urine and the birth of a previous sibling with GBS disease. This research project sought to generate essential epidemiological and virulence-related information about GBS isolates associated with invasive disease in Ireland.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin